Islamic Finance and Halal Investment Trends in the Digital Era: A Bibliometric Review (2010–2025) - Judijanto, Loso; Khotijah, Nur; Febrina, Ilza; Mayasari, Eny; Budiman, Mamdukh (Westscience Press, 2025)
This study offers a bibliometric analysis of Islamic finance and halal investment trends in the digital age (2010–2025), utilizing data from Scopus and examined with VOSviewer and Biblioshiny. The results indicate five predominant research themes: fintech and digital innovation, blockchain and cryptocurrency, financial inclusion and sustainability, Shariah governance, and Islamic investment ecosystems. Findings indicate that Malaysia and Indonesia spearhead worldwide research collaboration, connecting Southeast Asia, the Middle East, and Europe. Scholarship has progressively transitioned from traditional Islamic banking and sukuk to digital transformation, ethical finance, and sustainable development. The report offers pragmatic insights for policymakers and practitioners to advance Shariah-compliant financial innovation, while promoting financial inclusion and sustainable investment. It proposes a Digital Maqasid Finance Framework that amalgamates technology with Islamic ethical and social principles. This research provides a robust framework for future investigations into AI-driven Shariah compliance, digital halal finance, and sustainable Islamic investment ecosystems, despite limitations in database and time.